TOTAL POWER OF HEART RATE VARIABILITY AND CLINICAL EFFECIANCY OF AMLODIPIN IN ADVANCED PATIENTS WITH ARTERIAL HYPERTENSION - Аnufrieva, L.V.; Yabluchansky, M.I.; Bychkova, О.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Twenty patients (average age 63,25±5,4 years) with arterial hypertension I-III stage were outclinic observed. Estimated parameters were levels systolic and diastolic blood pressure, frequency of heart beats, general index of quality of life (GIQL) and parameters of a spectral analysis heart rate variability (HRV) before treatment, on a background of therapy and in acute pharmacological test (APT) with amlodipin. Depending on reaction of total power (ТР) of a spectrum HRV in APT all patients were divided into 2 groups: with positive and negative reaction ТР. Irrespective of a type of reaction ТР HRV in APT and on a background of therapy at all patients were marked authentic rising GIQL and high clinical efficiency amlodipin. The most expressed and the early hypotensive effect were marked in group of the patients with negative reaction ТР HRV.